Arginine:Glycine Amidinotransferase Is Essential for Creatine Supply in Mice During Chronic Hypoxia - Hannemann, Juliane; Cordts, Kathrin; Seniuk, Anika; Choe, Chi-un; Schmidt-Hutten, Lena; Duque Escobar, Jorge; Weinberger, Florian; Böger, Rainer; Schwedhelm, Edzard (Frontiers in Physiology, 2021)
Objective: Chronic hypoxia induces pulmonary and cardiovascular pathologies, including pulmonary hypertension (PH). L-arginine:glycine amidinotransferase (AGAT) is essential for homoarginine (hArg) and guanidinoacetate synthesis, the latter being converted to creatine by guanidinoacetate methyltransferase. Low hArg concentrations are associated with cardiovascular morbidity and predict mortality in patients with PH. We therefore aimed to investigate the survival and cardiac outcome of AGAT knockout (Agat−/−) mice under hypoxia and a possible rescue of the phenotype. Methods:Agat−/− mice and wild-type (WT) littermates were subjected to normoxia or normobaric hypoxia (10% oxygen) for 4 weeks. A subgroup of Agat−/− mice was supplemented with 1% creatine from weaning. Survival, hematocrit, blood lactate and glucose, heart weight-to-tibia length (HW/TL) ratio, hArg plasma concentration, and Agat and Gamt expression in lung, liver, and kidneys were evaluated. Results: After 6 h of hypoxia, blood lactate was lower in Agat−/−-mice as compared to normoxia (p < 0.001). Agat−/− mice died within 2 days of hypoxia, whereas Agat−/− mice supplemented with creatine and WT mice survived until the end of the study. In WT mice, hematocrit (74 ± 4 vs. 55 ± 2%, mean ± SD, p < 0.001) and HW/TL (9.9 ± 1.3 vs. 7.3 ± 0.7 mg/mm, p < 0.01) were higher in hypoxia, while hArg plasma concentration (0.25 ± 0.06 vs. 0.38 ± 0.12 μmol/L, p < 0.01) was lower. Agat and Gamt expressions were differentially downregulated by hypoxia in lung, liver, and kidneys. Conclusion:Agat and Gamt are downregulated in hypoxia. Agat−/− mice are nonviable in hypoxia. Creatine rescues the lethal phenotype, but it does not reduce right ventricular hypertrophy of Agat−/− mice in hypoxia.